A 14C-DATING AND OXYGEN-ISOTOPE DIAGRAM OF A HOLOCENE-REFORMED ICE WEDGE ON THE CHARA RIVER (TRANSBAIKAL REGION) - Vasil'chuk Yu.K.; Zaitsev V.N.; Vasil'chuk A.C. (My University, 2006)
The purpose of our work is to refine the age of the Holocene polygonal ice wedge complex in Terrace 1 of the Chara River, plot an isotope diagram, which allows one to reconstruct winter temperatures of the period of ice-wedge formation, and prove the possibility of active formation of ice wedges in the Holocene Optimum in even the southern regions of Siberia.
Keywords: Chara river; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен